Magnetically-accelerated photo-thermal conversion and energy storage based on bionic porous nanoparticles - Shi, Lei; Hu, Yanwei; Feng, Daili; He, Yurong; Yan, Yuying (Elsevier, 2020)
Recently, the technology of mixing phase change materials with high thermal conductivity fillers was developed, which has allowed thermal energy storage to be implemented in a wide range of industrial technologies and processes. In the present study, a hierarchical bionic porous nano-composite was prepared, which efficiently merged the nanomaterial characteristics of magnetism and high thermal conductivity in order to form a magnetically-accelerated solar-thermal energy storage method. The morphology and thermo-physical properties of materials were analysed. The experimental outcomes of phase change heat transfer demonstrated that the maximum storage efficiency increases by 102.7% when the hierarchical bionic porous structure is used, and a further 27.1% improvement can be achieved with the magnetic field. At the same time, the heat transfer process of energy storage in hierarchical porous composites under external physical fields is explained by simulation. Therefore, this magnetically-accelerated method demonstrated the superior solar-thermal energy storage characteristics within a hierarchical bionic porous structure which is particularly beneficial for the utilisation of solar direct absorption collectors and energy storage technology.